Of Young/Old Queens and Giant Dwarfs: A Critical Reading of Age and Aging in Snow White and the Huntsman and Mirror Mirror - Wohlmann, Anita (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
In 2012, the story of Snow White was retold twice in major Hollywood productions, featuring Charlize Theron and Kristen Stewart in Snow White and the Huntsman and Julia Roberts in Mirror Mirror. Why do we keep retelling this particular fairy tale? Researchers have argued that the tale speaks to current anxieties about old age and aging. While critics have been disappointed by the retroactive ways in which age, aging and gender are represented, this article argues that both movies negotiate these topics more ambivalently than one might assume at frst. This idea is explored, on the one hand, through an analysis of the role of hyperbole, masquerade and performativity, which are read as instances of potential counternarratives or subtexts of parody and resistance. On the other hand, the article zooms in on how the representation of the dwarfs in the two movies contributes to a deconstruction of age norms. In applying concepts of liminality, the article demonstrates in the last section how the dwarfs challenge stereotypical notions associated with youthfulness and adulthood by revealing the artifcial nature of age stages and thus allowing for a different access to some of the ageist implications of the 2012 representations of the tale.